The Effect of Marigold Leaves (Tagetes Erecta) Extract to Aedes Sp.Mosquito Mortality for the Biology Learning Source of Module Form - Marlina Kamelia (Universitas Muhammadiyah Prof. Dr. Hamka, 2020)
Background: Indonesia is rich in plants, one of which is leaf drop shit (Tagetes erecta) which has the potential as a vegetable insecticide. Diverse local plants will be very good if integrated in learning through modules so that they can help preserve local plants. The objectives of this study are: (1) to determine the effect of Tahitian Kotok (T. erecta) leaf extract on the mortality of Aedes sp. Mosquitoes. (2) determine the concentration of leaf extract of Tahitian Kotok (T. erecta) which can influence the mortality of Aedes sp. (3) compile teaching materials in the form of modules. Methods: This research is an experiment that is giving treatment and observation of Aedes sp. with 3 extractions of Kotok Tahi (T. erecta) leaves and 1 control treatment. The study was conducted with 4 replications, each: treatment 1 (0.5%), treatment 2 (1.3%), and treatment 3 (2%). The results of experimental research are then used as a basis for making modules and their feasibility tested. Results: Based on the research data there is a very significant effect on mortality resulting from each given extraction concentration. Based on research at a concentration of 2%, the highest mortality effect from Aedes sp. that is, with an average of 92.5% with 37 deaths from 40 mosquitoes. Kotok (T erecta) leaf extraction can be used as an alternative in controlling Aedes sp. Conclusion: The results of the study can be used as learning resources in the form of modules and are feasible to use with the validation results of 85.2%.